Alterations of Gut Microbiome and Metabolite Profiles Associated With Anabatic Lipid Dysmetabolism in Thyroid Cancer - Lu, Ganghua; Yu, Xiaqing; Jiang, Wen; Luo, Qiong; Tong, Junyu; Fan, Suyun; Chai, Li; Gao, Dingwei; Qiao, Tingting; Wang, Ru; Deng, Chengwen; Lv, Zhongwei; et al. (Frontiers in Endocrinology, 2022)
Background: Currently, the high morbidity of individuals with thyroid cancer (TC) is an increasing health care burden worldwide. The aim of our study was to investigate the relationship among the gut microbiota community, metabolites, and the development of differentiated thyroid cancer (DTC). Methods: 16S rRNA gene sequencing and an integrated LC–MS-based metabolomics approach were performed to obtain the components and characteristics of fecal microbiota and metabolites from 50 patients with TC and 58 healthy controls (HCs). Results: The diversity and richness of the gut microbiota in the TC patients were markedly decreased. The composition of the gut microbiome was significantly altered, and the Bacteroides enterotype was the dominant enterotype in TC patients. Additionally, the combined model (3 genera and 8 metabolites) and the metabolite model (6 metabolites) were markedly better than the microbial model for predicting TC. LEfSe analysis demonstrated that flora (g_Christensenellaceae_R-7_group, g_Eubacterium_coprostanoligenes_group) and metabolites (27-hydroxycholesterol, cholesterol) closely related to lipid metabolism were greatly reduced in the TC group. In addition, a clinical serum indicator (total cholesterol) and metabolites (27-hydroxycholesterol; cholesterol) had the strongest influence on the sample distribution. Furthermore, functional pathways related to steroid biosynthesis and lipid digestion were particularly inhibited in the TC group. In the microbiota-metabolite network, 27-hydroxycholesterol was significantly related to metabolism-related microorganisms (g_Christensenellaceae_R-7_group). Conclusions: Our research explored the characteristics of the gut microecology of patients with DTC. The findings of this study will help to further explore the microscopic world to discover risk factors that affect the occurrence and development of TC in the intestinal microecology.